Obstacles To Lending Commercial Banks To Small And Medium Enterprises In Light Of The Syrian War (Field Study On Private Syrian Commercial Banks) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The study aimed to clarify the obstacles facing small and medium-sized enterprise lending and to indicate some solutions that may help reduce the effects or remove the effects of this problem, especially in developing countries, with the most important reasons facing individuals (owners of small and medium enterprises) in financing their projects.The researcher relied on the deductive approach. She also relied on the descriptive approach to characterize and analyze the study variables based on the primary data collected, as it was relied upon to conduct a field study on Syrian private commercial banks in Latakia Governorate to collect the necessary initial data.The study found a set of results, including: Among the obstacles that stand in the way of granting loans to finance small and medium enterprises are factors related to the project itself, and among the obstacles that stand in the way of granting loans to finance small and medium enterprises is the factors related to the institutions that give the loan, and among the obstacles What stands in the way of granting loans to finance small and medium enterprises is the deficiencies of small and medium enterprises.